Inclusive Education in Early Childhood Care and Education: Policy and practice? - FAGAN, ELAINE (Trinity College (Dublin, Ireland). School of Education, 2022)
In Ireland, there have been significant changes in Early Childhood Education from legislative changes (Child Care Act, 1991, EPSEN Act, 2004, Disability ACT, 2005 & Pre-School Regulations, 2016) and the introduction of frameworks that support the delivery of early childhood education (Síolta, 2006 & Aistear 2009). Additionally, there has been a significant shift towards including special education needs children in mainstream education. While there is still a two-tier education system, from special education schools to mainstream educational settings with special classrooms and inclusion in the mainstream classroom, the full inclusion of children is the goal (Ring & O’Sullivan, 2019; Chadwell, Roberts & Daro, 2020). This dissertation will explore the early year's teachers (EYT) understanding of national policy and its implications on practice. The researcher will also explore inclusion in early years education, asking questions about how supported and understood. Participants participated in a qualitative research study to investigate policy and inclusion from the perspective of early-year teachers. Interviews were conducted through Zoom international. Using a thematic analysis approach, the researcher analysed the data. The themes identified through this analysis are as follows: relationships and pedagogy, qualifications, the experience of special education needs, daily routine, legislation and policy, setting policy, inclusion and supporting inclusion. Following the generation of these, the researcher conducted a detailed review of the data. The findings found that early years teachers understood inclusion well but were not confident about national policy and its implications. Further exploration on inclusion and supporting special education needs found that the early year teachers expressed a lack of education, resources and professional support, limiting their ability to support the child with special education needs. The findings indicated a need for investment in upskilling the workforce and investment in continuous professional development to ensure that early years teachers met the needs of all children in the Early Childhood Care and Education programme. The limitations of the study are also acknowledged.
Keywords: Special Education; Education